2014
DOI: 10.1002/jcp.24544
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Selectively Disrupts Brain Microvascular Endothelial Tight Junction Complexes Through a Hypoxia‐Inducible Factor‐1 (HIF‐1) Dependent Mechanism

Abstract: The blood-brain barrier (BBB) constitutes a critical barrier for the maintenance of central nervous system homeostasis. Brain microvascular endothelial cells line the vessel walls and express tight junction (TJ) complexes that restrict paracellular passage across the BBB, thereby fulfilling a crucial role in ensuring brain function. Hypoxia, an impaired O(2) delivery, is known to cause BBB dysfunction but the mechanisms that drive this disruption remain unclear. This study discloses the relevance of the master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 52 publications
10
107
0
1
Order By: Relevance
“…However, most of these studies were focused on epithelial TJs, and therefore, the role of phosphorylation of TJ proteins in the preservation or perturbation of endothelial TJ integrity and its barrier function has not been well-studied. In this context, a few studies, including ours, showed that phosphorylation of TJ proteins leads to endothelial TJ disruption and loss of its barrier function ( 20,21,42,43 ). In the present study, we have extended our previous observations on the role of tyrosine phosphorylation of TJ proteins in the disruption of TJ integrity and barrier function to JamA.…”
Section: Xo-dependent Ros Production Mediates 15(s)-heteinduced Jama supporting
confidence: 81%
“…However, most of these studies were focused on epithelial TJs, and therefore, the role of phosphorylation of TJ proteins in the preservation or perturbation of endothelial TJ integrity and its barrier function has not been well-studied. In this context, a few studies, including ours, showed that phosphorylation of TJ proteins leads to endothelial TJ disruption and loss of its barrier function ( 20,21,42,43 ). In the present study, we have extended our previous observations on the role of tyrosine phosphorylation of TJ proteins in the disruption of TJ integrity and barrier function to JamA.…”
Section: Xo-dependent Ros Production Mediates 15(s)-heteinduced Jama supporting
confidence: 81%
“…Hypoxia [21,25,[168][169][170] and ischemia [171] have been shown to induce BBB permeability by altering the expression of junctional proteins. Importantly, the combined effect of hypoxia and aglycemia appears to enhance the increased BBB permeability produced by hypoxia alone [172].…”
Section: Endothelial Response To Chronic Hypoperfusion-related Hypoximentioning
confidence: 99%
“…Hypoxia induces BBB permeability [21,25,[168][169][170], ROS generation [160,161] and stimulates proinflammatory gene expression [18,162]. Hypoxia and inflammation may cooperate in inducing BBB permeability [21].…”
Section: Hypoxia/ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke results in the breakdown of the BBB, with subsequent damage to cerebral vasculature and nonvascular brain elements, including neurons, astrocytes, and microglia. Hypoxia‐induced vascular damage is associated with disruption of paracellular cell junctions, with selective targeting of brain microvascular endothelial TJ complexes 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%